Developing Tools and Resources for Those in Practice. - Bourne, Stephen; Neville-Neil, George (Communications of the ACM, 2013)
The authors, chair and co-chair of the Association for Computing Machinery's (ACM's) Practitioner Board, discuss the services their board offers to computer programmers and software developers, and the board's strategic planning to encourage more young software practitioners to join ACM. Professional development services, computer profession advocacy, and ACM certification programs are mentioned, as well as webinars for subjects such as cloud computing on mobile devices.